Nitazoxanide against COVID-19 in three explorative scenarios - Meneses Calderón, José; Figueroa Flores, Ma. del Rocío; Paniagua Coria, Leopoldo; Briones Garduño, Jesús Carlos; Meneses Figueroa, Jazmín; Vargas Contretas, María José; de la Cruz Ávila, Lilia; Díaz Meza, Salvador; Ramírez Chacón, Reynaldo; Padmanabhan, Srivatsan; Mendieta Zerón, Hugo (The Journal of Infection in Developing Countries, 2020)
Introduction: Nitazoxanide has shown efficacy in vitro against coronavirus infections (MERS, SARS, SARS-CoV-2). The aim of this report is to describe the results of treating COVID-19 positive patients with nitazoxanide in three clinical settings: pregnancy/puerperium, hospitalized patients in an Internal Medicine Service and in an ambulatory setting. Methodology: This was a prospective follow-up and report of COVID-19 cases in three different situations, pregnant women, hospitalized patients receiving medical attention in an Internal Medicine Service and ambulatory patients residing in Toluca City, and Mexico City. Results: The experience with a first group of 20 women, pregnant (17) or in immediate puerperium (3) was successful in 18 cases with two unfortunate deaths. The five cases treated in an Internal Medicine service showed a positive outcome with two patients weaned from mechanical ventilation. Of the remaining 16 patients treated in an ambulatory setting, all got cured. Nitazoxanide seems to be useful against SARS-CoV-2, not only in an early intervention but also in critical condition as well as in pregnancy without undesired effects for the babies. As an adjunctive therapy budesonide was used that seems to contribute to the clinical improvement. Conclusions: Nitazoxanide could be useful against COVID-19 as a safe and available regimen to be tested in a massive way immediately.